As medidas de urgência no processo administrativo disciplinar : uma análise de seu cabimento a partir do modelo processual constitucional - Simon, Lidia Lara Araujo de Oliveira e Souza Wernersbach (2015)
Ample is the doctrine on preventive and advanced relief, as well as large are the teachings of the administrative process, but few writings that willing to consider both issues at the same time are found. So, the main scope of this study is to stimulate discussion about the possibility, feasibility, and, perhaps, necessity to grant immediate injunctions (preventive or advanced) in the course of the disciplinary administrative process. For that, we will make, initially, some notes over the immediate injunctions, stressing, therefore, its concepts, requirements and objectives. We will also expound on the administrative process and its constitutional status, so that later we can merge these subjects and reflect about the pro and con arguments to the assumption raised. Finally, the conclusion that will reach, which is that it is indeed possible for the Administration to grant, itself, immediate injunctions, will result of a logical-deductive construction derived from premises established in the course of this study.